(untitled) (Journal of Human Sciences, 2020)
Many philosophers used to present their theory of thought over the rest of philosophy, thus, it is not possible for the philosopher to engage in researching an issue of philosophy unless s/he is able to draw the features of her/his epistemology. Based on this theory, her/his position on other issues of philosophy is determined. From here, you take Epistemology: its role and importance in any philosophical system that the philosopher establishes. Descartes realized the importance of epistemology in building any new philosophical system, thus, he devoted a large part of his philosophy to researching the issue of knowledge, and by relying on it, he determined his position on a number of intellectual issues before him, including the issue of scholastic philosophy. This last aspect, controlled the Western thought for a long period of time, and was able to draw his features and path, for this, and to establish his new philosophy. Descartes had to break with this philosophy to establish a new philosophy that responds to the demands of his time. And to accomplish this matter, he had to define his position on the nature and content of the language, as this latter is the template that will enable him formulating his philosophical and scientific ideas and theories. The goal behind this research is to diagnose the nature of the relationship between the theory of thought on the one hand, and language on the other hand, in Descartes’ rational philosophy.